2014
DOI: 10.1155/2014/650393
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variants ofADIPOQand Association with Type 2 Diabetes Mellitus in Taiwan Chinese Han Population

Abstract: Diabetes is a serious global health problem. Large-scale genome-wide association studies identified loci for type 2 diabetes mellitus (T2DM), including adiponectin (ADIPOQ) gene and transcription factor 7-like 2 (TCF7L2), but few studies clarified the effect of genetic polymorphisms of ADIPOQ and TCF7L2 on risk of T2DM. We attempted to elucidate association between T2DM and polymorphic variations of both in Taiwan's Chinese Han population, with our retrospective case-control study genotyping single nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
6
16
0
1
Order By: Relevance
“…KCNJ11 gene Glu23Lys polymorphic marker's association with T2D is likely associated with the replacement of glutamate with lysine in the 23rd position of Kir 6.2 protein, which results in suppressed insulin blood secretion as a result of increased ATP‐dependent ionic channel activity, membrane potential change and intracellular calcium concentration decrease, which initiates insulin secretion . The association of ADIPOQ gene G276T polymorphic locus with T2D in our study was also previously confirmed in the Japanese and Taiwanese, and such association may be explained with impaired tissue susceptibility to insulin …”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…KCNJ11 gene Glu23Lys polymorphic marker's association with T2D is likely associated with the replacement of glutamate with lysine in the 23rd position of Kir 6.2 protein, which results in suppressed insulin blood secretion as a result of increased ATP‐dependent ionic channel activity, membrane potential change and intracellular calcium concentration decrease, which initiates insulin secretion . The association of ADIPOQ gene G276T polymorphic locus with T2D in our study was also previously confirmed in the Japanese and Taiwanese, and such association may be explained with impaired tissue susceptibility to insulin …”
Section: Discussionsupporting
confidence: 78%
“…Genetic predisposition to T2D was studied widely during the last decades . At present, around 50 candidate genes are considered to increase the likelihood of T2D, of which adiponectin gene ( ADIPOQ ), potassium channel, inwardly rectifying subfamily J, member 11 ( KCNJ11 ) and transcription factor 7‐like 2 ( TCF7L2 [IVS3C>T]) may be associated with insulin resistance and β‐cells dysfunction . Carriage of various SNP combinations may explain clinical heterogeneity of this disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome‐wide association studies identified genetic variants in the adiponectin gene ( ADIPOQ ) associated with blood levels of adiponectin . The ADIPOQ variants have also been related to other metabolic disorders such as diabetes and insulin resistance . Among these genetic variants, one SNP rs864265, located 5 kb upstream of the widely discussed ADIPOQ promoter region and 16 kb upstream of the translation start site (chr3: 188 036 986), showed the strongest association with plasma adiponectin, also associated with insulin resistance and diabetes‐related metabolic traits .…”
mentioning
confidence: 99%
“…[8][9][10][11][12] The ADIPOQ variants have also been related to other metabolic disorders such as diabetes and insulin resistance. [13][14][15] Among these genetic variants, one SNP rs864265, located 5 kb upstream of the widely discussed ADIPOQ promoter region and 16 kb upstream of the translation start site (chr3: 188 036 986), showed the strongest association with plasma adiponectin, also associated with insulin resistance and diabetes-related metabolic traits. 11,12 However, data are scarce on the relationship between ADIPOQ variants and markers of early-stage atherosclerosis.…”
mentioning
confidence: 99%